Pengaruh Rotasi Auditor, Proffesional Care, Latar Belakang Pendidikan dan Etika Profesional terhadap Kualitas Audit - Aditya Wahyu Dewanggajati (Jurnal Akuntansi dan Bisnis, 2014)
The purpose of this study was to find out the effect of auditor rotation, professional care, education background and professional ethic of auditors in The Audit Board of Republic of Indonesia (BPK RI) toward audit quality The sample of this study were sector public auditors of The Audit Board of The Republic of Indonesia. This study used survey method by distributing questionnaires and used the multiple linier regression analysis with the significance level (α) of 5%. This study has shown that auditor rotation, professional care and professional ethic had positive significant effect toward quality and educational background has no significant effect toward audit quality.